The effect of fraud detection skills in the settlement of Compensatory claims for the fire and accident insurance portfolio: An applied study in the national and Iraqi insurance companies (Journal of Accounting and Financial Studies ( JAFS ), 2018)
The research seeks to identify the impact of fraud detection skills in the settlement of compensatory claims for the fire and accident insurance portfolio and the reflection of these skills in preventing and reducing the payment of undue compensation to some who seek profit and enrichment at the expense of the insurance contract. And compensatory claims in the portfolio of fire and accident insurance in the two research companies, which show the effect and positive return of the detection skills and settlement of the compensation on the amount of actual compensation against the claims inflated by some of the insured, The research sample consisted of (70) respondents from a community size (85) individuals between the director and assistant director and staff (branch - The Department) of Fire and Accident Insurance in the two sample companies. The questionnaire was distributed to them for the purpose of testing two main hypotheses related to the relationship of correlation and influence between the two main research variables. The researcher also found a correlation relationship between the two variables, Search based on the net Research findings.